Body composition and basal metabolic rate in pregnant women - Bhardwaj, Shaila; Verma, Deepali; Kapoor, Satwanti (Anthropological Review, 2013)
Pregnancy, a milieu of physiological and metabolic adaptation, is associated with enhanced basal metabolic rate by alteration in maternal tissue and metabolism to ensure foetal growth and development. A cross-sectional study of Indian Baniya females was conducted to assess the relationship between basal metabolic rate and body composition during pregnancy. The 20–40 year old female subjects were broadly categorized in two groups; pregnant (N=198) and non-pregnant (N=35).Anthropometric measurements of each subject included height and weight, with basal metabolic rate (BMR), fat mass (FM), fat-free mass (FFM) and total body water (TBW) assayed by bioelectric impedance body composition analyzer. The descriptive statistics revealed pregnancy associated weight gain, increased FFM, FM, TBW and BMR with marked changes during the second and third trimesters. Although multiple linear regression analysis showed substantial change in BMR due to both FM and FFM, fat-free mass contributed to a much lesser extent. Pregnancy, as an anabolic phase of the female reproductive cycle, is associated with metabolic flexibility which alters the relationship between body composition and BMR. These findings however require further validation in longitudinal design studies.